Evidence-based general practice: a scoping review - Yu Cheng; Chuan Zou; Chaojie Liu; Yu Jia; Rong Yang; Yonggang Zhang; Jianjun Han; Yi Lei; Xiaoyang Liao (BMC Primary Care)
Abstract Background Evidence-based medicine(EBM) is widely used across various disciplines globally. However, in general practice, we need a more person-centered approach rather than a disease-centered one. The differentiation of evidence-based general practice (EBGP) is essential. This scoping review aims to extract a potential definition of EBGP and uncover its characteristics in implementation. Methods We conducted a comprehensive search across three databases - PubMed, Embase, and Cochrane Library - spanning from the inception of these databases to September 24, 2023. The inclusion criteria encompassed studies focusing on EBM in general practice, involving general practitioners as study participants, and reporting any aspects related to providing evidence-based care. Our screening process involved evaluating titles, abstracts, and full texts to extract definitions and characteristics from all relevant records discussing EBGP. These identified characteristics were then categorized and thematically grouped following the guidelines outlined in the Consolidated Framework for Implementation Research (CFIR). Results We initially retrieved 20,263 records from the original search. Among these, 40 records aligned with our inclusion criteria. The majority of these records took the form of reviews, qualitative studies, comments, cross-sectional surveys, or editorials. From these 40 studies, we extracted 33 unique characteristics of EBGP. Subsequently, these characteristics were thematically grouped into 19 categories, which fell under five overarching themes: evidence base, GP’s role, person’s role, care process, and care environment. Conclusions We propose the following definition for EBGP: Applying a combination of the best available evidence, integrated within the inner and outer contexts of general practice, person preferences, and the expertise of the general practitioner to formulate shared, person-centered decisions aimed at holistic care. This definition provides a solid foundational framework for the development of EBGP guidelines and policies. Registration number https://doi.org/10.17605/OSF.IO/2UNX7 .